2017
DOI: 10.1111/php.12775
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of Fluorescence Quenching of Reduced Nicotinamide Adenine Dinucleotide by Oxamate in Lactate Dehydrogenase Ternary Complexes

Abstract: Fluorescence of Reduced Nicotinamide Adenine Dinucleotide (NADH) is extensively employed in studies of oxidoreductases. A substantial amount of static and kinetic work has focused on the binding of pyruvate or substrate mimic oxamate to LDH•NADH where substantial fluorescence quenching is typically observed. However, the quenching mechanism is not well understood limiting structural interpretation. Based on time-dependent density functional theory (TDDFT) computations with cam-B3LYP functional in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Binding of pyruvate, the substrate, or oxamate, a structural analogue, 23,24 has been observed to quench strongly the cofactor fluorescence by a possible photoinduced electron transfer process. 41,42 Introduction of an inhibitor that binds in the active site, displacing the bound oxamate, would alleviate that quenching. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of pyruvate, the substrate, or oxamate, a structural analogue, 23,24 has been observed to quench strongly the cofactor fluorescence by a possible photoinduced electron transfer process. 41,42 Introduction of an inhibitor that binds in the active site, displacing the bound oxamate, would alleviate that quenching. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have studied the affinity of oxamate for two LDH orthologs in the temperature range preceding denaturation. Binding of the substrate to the LDH/NADH binary complex strongly quenches the emission of bound NADH, likely because of interactions with the polar groups of the substrate or its mimic, oxamate, with NADH. We observed the change in intensity of the 280 and 340 nm peaks (Figure ) to determine isotherms, the association constant, and the free energy for the binding of oxamate to the binary LDH/NADH complex (see Experimental Procedures). van’t Hoff analysis (eq ) in the temperature range of 20–35 °C reveals the association enthalpy of the ternary complexes containing phLDH and cgLDH, and the association entropy was calculated using the Gibbs equation (see Experimental Procedures) (Figure and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we have shown that oxamate could be an electron acceptor in the quenching of NADH fluorescence when bound to ternary lactate dehydrogenase (LDH) complexes. 16 This prompts us to consider that the quenching of tryptophan fluorescence by oxamate is also a result of photoinduced electron transfer (PET).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, as has been shown previously, the correlation between the energies of frontier orbitals of quenchers and Stern−Volmer constants can be established when PET is responsible for the fluorescence quenching. 16 By comparing the frontier orbital energies of quenchers, one then could tell whether a molecule can be a PET donor or acceptor in fluorescence quenching qualitatively or even quantitatively. We apply this concept to the study of the quenching of tryptophan fluorescence by oxamate and pyruvate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation